2015
DOI: 10.4049/jimmunol.1402354
|View full text |Cite
|
Sign up to set email alerts
|

Complement Deficiency Promotes Cutaneous Wound Healing in Mice

Abstract: Wound healing is a complex homeostatic response to injury that engages numerous cellular activities, processes, and cell-to-cell interactions. The complement system, an intricate network of proteins with important roles in immune surveillance and homeostasis, has been implicated in many physiological processes; however, its role in wound healing remains largely unexplored. Here we employ a murine model of excisional cutaneous wound healing and show that C3−/− mice exhibit accelerated early stages of wound heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 47 publications
2
52
0
1
Order By: Relevance
“…Given their simultaneous activation at the site of injury, crosstalk between complement, coagulation pathways and TLRs might be particularly relevant in this setting 89 . Interestingly, findings from animal studies suggest that complement might also influence the repair process after trauma by inducing osteoclastogenesis and contributing to wound healing 89,90 . A 2015 study of spinal cord injury in mice showed that early inhibition of C5aR1 during the acute phase of injury improved clinical outcomes, whereas extended blockade during the chronic phase of injury did not, indicating dual roles for complement in inflammation and repair 91 .…”
Section: Complex Involvement In Clinical Disordersmentioning
confidence: 99%
“…Given their simultaneous activation at the site of injury, crosstalk between complement, coagulation pathways and TLRs might be particularly relevant in this setting 89 . Interestingly, findings from animal studies suggest that complement might also influence the repair process after trauma by inducing osteoclastogenesis and contributing to wound healing 89,90 . A 2015 study of spinal cord injury in mice showed that early inhibition of C5aR1 during the acute phase of injury improved clinical outcomes, whereas extended blockade during the chronic phase of injury did not, indicating dual roles for complement in inflammation and repair 91 .…”
Section: Complex Involvement In Clinical Disordersmentioning
confidence: 99%
“…C3, which is hyperexpressed in human psoriatic epidermis, is also aberrantly upregulated in a mouse psoriasis model by calprotectin (S100A8-S100A9 complex) and drives the disease phenotype 37 . Complement also influences cutaneous wound healing, where C3 –/– and C5ar1 –/– mice exhibit an accelerated healing phenotype, suggesting that recruitment and activation of inflammatory cells to the wound might delay the healing process 38 .…”
Section: Complement In Homeostatic Immunity and Microbial Evasionmentioning
confidence: 99%
“…Additionally, the healing kinetics of the two groups were statistically similar until day 8[39]. The complement cascade is rapidly activated in response to wounding[40], and it has been shown that mice deficient in C3 or C5 displayed accelerated wound healing in the early stages (days1-3) of normal wound healing[41]. Therefore, the critical aspect in determining the efficacy of complement as a therapeutic target was to evaluate the kinetics of C5 and C3a in the initial 48 hours post-wounding in both normal and diabetic wounds, and if inhibition of C1 could reestablish levels seen in normal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Complement can be activated by the classical, lectin or alternative pathways, but most commonly activation is triggered by the classical or lectin pathways with the alternative pathway functioning as a positive-feedback loop[15]. Complement activation occurs in skin wounds and has been shown to contribute to altered wound healing in several models including burn wounds[1619]. It is likely that complement plays multiple roles in a wound including innate immune protection against infection as well as potentially inhibiting healing if activation is dysregulated.…”
Section: Introductionmentioning
confidence: 99%